Variação temporal da estrutura do solo em sistemas integrados de cultivo da cebola no Uruguai - Corcini, Adão Leonel Mello (2008)
The social and economical importance of onion in Uruguai is very relevant. The soil mobilization and ridge till are crucial to reduce bulk density and increase the macro/micropores relation for Argiudoll, to induce conditions for a normal growth and development for most crops. The objectives of this study were to measure the effects of soil and plant management on aggregate stability, organic matter and some soil physico-hydric properties as porosity, bulk density, water retention curve, air permeability and water conductivity. Two experiments from National Institute of agriculture investigation (INIA) initiated in 1995 were used. Experiment one used the following treatment: 1) alfalfa; 2) festuca; 3) birdfoot trefoil, alfalfa and white clover mixture; 4) onion after alfalfa; 5) onion after festuca; 6) onion after plant mixture. The experiment two used the following treatments: Summer season - 1) fallow; 2) feijão; 3) corn; 4) setaria. During winter season onion was cultivated at all plots. In both experiments the plots were split to receive 0, 80 and 120 kg de N ha-1. To measure aggregate stability and organic matter preserved three soil samples from each plot were taken from 0-0.05 m layer. To measure soil physico-hydric properties samples were taken using metalic rings from 0-0.01 and 0.1-0.2 m layers. The variation of water stable aggregates were higher than of dry stable aggregates. The stability index was higher for pastures in the experiment I and for fallow in the experiment II, implying lower aggregates impact due tillage or higher organic matter addition by plants on soil surface. However, there is clear indication that tillage was necessary, in order to improve macroporosity, hydraulic conductivity and air permeability.